2002
DOI: 10.3386/w9108
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Social Return to Higher Education: Evidence From Longitudinal and Repeated Cross-Sectional Data

Abstract: for many useful suggestions on this and an earlier draft. All errors are naturally my own. Financial support from the A. P. Sloan Dissertation Scholarship is gratefully acknowledged. The views expressed herein are those of the author and not necessarily those of the National Bureau of Economic Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
670
5
34

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 406 publications
(740 citation statements)
references
References 16 publications
31
670
5
34
Order By: Relevance
“…In addition, people with higher education may be more likely to make positive lobbies for improvements in the area (Galea and Ahern 2005), such as trigger actions that make it safer, more walkable and with better physical structure. Econometric studies have also shown that regions with higher education may lead to an increase in the average income of the region (Moretti 2004). Finally, high levels of education are usually associated with the acquisition of knowledge and engagement in healthy behaviors, and the interaction of people with different levels of education may allow the sharing and dissemination of knowledge and skills with potential positive effect on the health of everyone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people with higher education may be more likely to make positive lobbies for improvements in the area (Galea and Ahern 2005), such as trigger actions that make it safer, more walkable and with better physical structure. Econometric studies have also shown that regions with higher education may lead to an increase in the average income of the region (Moretti 2004). Finally, high levels of education are usually associated with the acquisition of knowledge and engagement in healthy behaviors, and the interaction of people with different levels of education may allow the sharing and dissemination of knowledge and skills with potential positive effect on the health of everyone.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between local human capital and wages does not need to be driven by externalities, as emphasized in Ciccone and Peri (2006) and Moretti (2003Moretti ( , 2004. Whenever workers with different levels of education are imperfect substitutes in production, the parameter η will pick up effects that can be driven both by "composition effects", due to a larger proportion of skilled workers on average productivity, and by genuine spillovers, due to human capital externalities.…”
Section: Imperfect Substitutability Across Workersmentioning
confidence: 93%
“…This survey is conduced every 2 years by the Bank of Italy on a representative 5 The definition of LLM is crucial to identify human capital externalities and, in general, all kinds of agglomeration effects: see Rosenthal and Strange (2003). Duranton (2004) argues that the mixed conclusions on education externalities in the US may well depend on the territorial unit adopted, such as US States in Acemoglu and Angrist (2000), and MAs in Ciccone and Peri (2006), Moretti (2004), andRauch (1993). 6 According to Lucas (1988), the effects of average skill on the productivity of each worker have to do with "the ways various groups of people interact, which may be affected by political boundaries but are certainly an entirely different matter conceptually."…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations